A centrifugal ice microtome for measurements of atmospheric CO2 on air trapped in polar ice cores - H. Fischer; T. F. Stocker; B. Bereiter (Atmospheric Measurement Techniques, 2013)
For atmospheric CO2 reconstructions using ice cores, the technique to release the trapped air from the ice samples is essential for the precision and accuracy of the measurements. We present here a new dry extraction technique in combination with a new gas analytical system that together show significant improvements with respect to current systems. Ice samples (3–15 g) are pulverised using a novel centrifugal ice microtome (CIM) by shaving the ice in a cooled vacuum chamber (−27 °C) in which no friction occurs due to the use of magnetic bearings. Both, the shaving principle of the CIM and the use of magnetic bearings have not been applied so far in this field. Shaving the ice samples produces finer ice powder and releases a minimum of 90% of the trapped air compared to 50%–70% when needle crushing is employed. In addition, the friction-free motion with an optimized design to reduce contaminations of the inner surfaces of the device result in a reduced system offset of about 2.0 ppmv compared to 4.9 ppmv. The gas analytical part shows a higher precision than the corresponding part of our previous system by a factor of two, and all processes except the loading and cleaning of the CIM now run automatically. Compared to our previous system, the complete system shows a 3 times better measurement reproducibility of about 1.1 ppmv (1 σ) which is similar to the best reproducibility of other systems applied in this field. With this high reproducibility, no replicate measurements are required anymore for most future measurement campaigns resulting in a possible output of 12–20 measurements per day compared to a maximum of 6 with other systems.